PERBANDINGAN PEMBAGIAN WARISAN UNTUK JANDA MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA DAN KOMPILASI HUKUM ISLAM - Riki Budi Aji; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Widow as heir there are many similarities and differences in system of Islamic law with Western legal system where people are less aware of the similarities and differences. Inheritance law provisions regarding inheritance for widows there are very significant differences between the provisions of the Civil Code and the laws of Islam. Based on the explanation and the above background, the authors are interested in the discussion raised in a scientific study entitled